Molecular Docking of Flavonoids from Extract of Roselle (Hibiscus sabdariffa L.) Calyx on PBP2a as the Basis for Antibacterial Activity Against Methicillin Resistant Staphylococcus aureus - Ramadhani, Firmansyah Ardian; Prastika, Marsha Fendria; Fikriyah, Nuril; Isnaeni; Diyah, Nuzul Wahyuning (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
The increasing bacterial resistances to antibiotics are serious threat to world health. In Indonesia, there are resistant bacteria such as Methicillin Resistant Staphylococcus aureus (MRSA). In order to overcome the problem, the compounds contained in the Hibiscus sabdariffa L. are potential to be developed as new antibacterial against MRSA. To confirm the antibacterial activity, the extract of roselle calyx was tested against MRSA. The twelve compounds contained in the extract was docked into binding site of PBP2a using Autodock 4.2.6. The results showed MIC 2.5% of roselle extract. Two flavonoid compounds comply the Lipinski’s rules and the docking results showed all compounds had higher binding affinity than reference ligand ceftobiprole. The quantitative structure-physicochemical property relationship (QSPR) found that steric property (CMR) and energy (Etotal) of ligand contributed to the binding affinity against PBP2a. It concluded kaempferol-rutinoside was the most potential compound from H. sabdariffa that could be selected as lead compound to be develop as antibacterial agents.